2017
DOI: 10.5296/jet.v4i2.10777
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Test Anxiety through the Testing Effect in Asynchronous, Objective, Online Assessments at the University Level

Abstract: Do asynchronous online evaluations, designed and delivered to engage the testing effect, moderate test anxiety? To answer this question, we surveyed 353 undergraduate and graduate students, drawn from 12 courses, hybrid and online, asking whether the option to take and retake a quiz lessened their text anxiety. Students, no matter the course or level, indicate yes, with more than 90% of the sample agreeing that the option to retake a quiz reduced test anxiety. We also consider this result with regards to the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…On the other hand, anxiety in physics of untreated students is not addressed specifically, because they do not receive in-class questioning and receive only selective feedback when asked for it. These assumptions are in line with the literature that a series of anonymous formative assessments with multiple-choice questions and explanatory group-feedback of teachers enables students to grow their self-confidence and improves their metacognitive skills that reduces anxiety (Brown et al 2014;Kornell and Son 2009;Sullivan 2017).…”
Section: Conclusion and Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…On the other hand, anxiety in physics of untreated students is not addressed specifically, because they do not receive in-class questioning and receive only selective feedback when asked for it. These assumptions are in line with the literature that a series of anonymous formative assessments with multiple-choice questions and explanatory group-feedback of teachers enables students to grow their self-confidence and improves their metacognitive skills that reduces anxiety (Brown et al 2014;Kornell and Son 2009;Sullivan 2017).…”
Section: Conclusion and Discussionsupporting
confidence: 67%
“…Arkin and Schumann (1984) and Rocklin and Thompson (1985) found that immediate explanatory feedback is associated with less anxiety. Furthermore, by explaining why an answer is correct or incorrect, students will improve their understanding of the course material, which reduces their anxiety and helps them to achieve a higher score in a subsequent attempt (Sullivan 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, anxiety in physics of untreated students is not addressed specifically, because they do not receive in-class questioning and receive only selective feedback when asked for it. These assumptions are in line with the literature that a series of anonymous formative assessments with multiple-choice questions and explanatory groupfeedback of teachers enables students to increase their self-confidence and improves their metacognitive skills that reduces anxiety (Brown, Roediger & McDaniel, 2014;Kornell & Son, 2009;Sullivan, 2017).…”
Section: Conclusion and Discussionsupporting
confidence: 70%
“…Although there is a concern that taking tests may increase test anxiety (Steele, 2011), two studies, employing questionnaires, demonstrated that students tend to believe that frequent tests can alleviate test anxiety (Agarwal, D'Antonio, Roediger, McDermott, & McDaniel, 2014;Sullivan, 2017). For instance, Sullivan (2017) asked 353 undergraduates and graduates if they agreed with the statement: The option to retake a quiz reduced my test anxiety. Over 90% of students agreed with this statement.…”
Section: Potential Effects Of Frequent Tests On Test Anxietymentioning
confidence: 99%